Pengaruh Disiplin dan Motivasi terhadap Prestasi Akademik Taruna dalam Simulasi Kehidupan Kapal di Kampus BP2IP Tangerang - Ratna Ika Setiyaningsih, Untari (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
This research aims to determine the influence between discipline and motivation to the academic achievement of the Taruna in the life of ship simulation on campus BP2IP Tangerang. This research is a quantitatif study with Taruna BP2IP Tangerang sample with a sampling technique. Data collection using surveys. Data analysis is using a Likert scale. The results of the research show that there is a partial direct positive influence between discipline and motivation to Taruna's academic achievement in the life simulation of the ship at BP2IP Tangerang Campus.